Self-assessment and clinical diagnosis of periodontal status among patients visiting dental institution in Bangalore city: a cross-sectional study - Devi, Rajkumari Surbala; Kumar, Manish; Nongmeikapam, Rejita; B., Rahul; S. G., Sushma; Devi, Priya (International Journal Of Community Medicine And Public Health, 2023)
Background: Periodontal diseases are a group of lesions affecting tissues surrounding and supporting the teeth. Periodontal diseases are considered as a group of highly prevalent infectious, inflammatory conditions of the supporting structures of the teeth which affects more than 50% of the world’s adult population. The present study was undertaken to evaluate the extent of agreement between clinical and self-assessed periodontal health status among patients visiting the outpatient department of Rajarajeswari Dental College and Hospital, Bangalore, India. Methods: A cross-sectional study was done among 250 patients who attended the outpatient department of Rajarajeswari Dental College and Hospital, Bangalore. The study population was subjected to a self-administered questionnaire which was followed by periodontal examination. The clinical examination included an assessment of the periodontal condition using CPI and mobility. Results: There was a marked discrepancy between the two values of self-assessed and clinically diagnosed periodontal health status which shows that the self-assessed periodontal tool was a poor indicator of the periodontal health status. Conclusions: The present study showed that there is a discrepancy between the subjectively and objectively assessed periodontal health status. Increasing people’s awareness and knowledge of their own dental disorders and changing their attitudes and behavior towards oral health care will help in improving oral as well as general health.